1985
DOI: 10.1007/bf00237678
|View full text |Cite
|
Sign up to set email alerts
|

Human ocular counterroll: assessment of static and dynamic properties from electromagnetic scleral coil recordings

Abstract: Static and dynamic components of ocular counterroll as well as cyclorotatory optokinetic nystagmus were measured with a scleral search coil technique. Static counterroll compensated for about 10% of head roll when the head was tilted to steady positions up to 20 deg from the upright position. The dynamic component of counterroll, which occurs only while the head is moving, is much larger. It consists of smooth compensatory cyclorotation opposite to the head rotation, interrupted frequently by saccades moving i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
157
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(172 citation statements)
references
References 27 publications
14
157
1
Order By: Relevance
“…4, A and B). When considering all subjects for whom we were able to obtain torsional data consistently (n ϭ 5), the average torsional gain (defined as peak torsional velocity over 60°/s peak stimulus velocity) for the upright trial in light was 0.054 Ϯ 0.013 for CW rotations and 0.044 Ϯ 0.016 for CCW rotations, consistent with previous studies (Cheung and Howard 1991;Collewijn et al 1985;Jackson 1992;Morrow and Sharpe 1989). The example in Figs.…”
Section: Eye Movement Responsessupporting
confidence: 87%
“…4, A and B). When considering all subjects for whom we were able to obtain torsional data consistently (n ϭ 5), the average torsional gain (defined as peak torsional velocity over 60°/s peak stimulus velocity) for the upright trial in light was 0.054 Ϯ 0.013 for CW rotations and 0.044 Ϯ 0.016 for CCW rotations, consistent with previous studies (Cheung and Howard 1991;Collewijn et al 1985;Jackson 1992;Morrow and Sharpe 1989). The example in Figs.…”
Section: Eye Movement Responsessupporting
confidence: 87%
“…20 Using an earth-fixed complex target at a distance of 1 m that has been shown to elicit higher gain in normal subjects, we recorded the eye movements of 18 patients with skew deviation and 18 normal participants by scleral search coil. 21 We found that mean OCR gain was reduced by 45% in patients as compared with normal controls, and that OCR gains were asymmetric between eyes and between torsional directions in 90% of patients. Our findings that patients with skew deviation had abnormally low and asymmetric OCR gain provided support to our second hypothesis that imbalance in the utriculo-ocular reflex pathway is a mechanism of skew deviation.…”
Section: Skew Deviationmentioning
confidence: 63%
“…[38][39][40] This torsional vestibulo-ocular reflex, termed ocular counterroll, however, compensates for only about 10% to 20% of the head tilt (eg, a 20° head tilt toward the right shoulder will result in the upper pole of both eyes to rotate 2° to 4° toward the left shoulder). [38][39][40] Static ocular counterroll is important from a clinical standpoint because this otolith-driven reflex forms the basis of the Bielschowsky head-tilt test and it explains the compensatory head tilt in patients with trochlear nerve palsy. In normal humans, for example, during right head tilt, the static ocular counterroll activates the right superior oblique and superior rectus muscles, causing the right eye to incyclotort and elevate slightly.…”
Section: Pathophysiologymentioning
confidence: 99%